Escola e prisão : paralelo político-institucional no Rio Grande do Sul (2007-2009) - Rocha, Henrique José da (2010)
Before the current condition that we encounter education in the state of Rio Grande do Sul, represented by their school institutions,this study assumes the existence of a arallel between prisons and schools from the state regarding to their physical structures. Admitting this possibility, firstly it‟s projected a fast genealogical analysis of the prison and education systems in Brazil and in the state, prioritizing the institution aspect, having the objective of identifying the aggravating that led the prison to its current situation, and by chance, finding historical resemblance in the education field regarding to schools. Given the historical period, prison and education of Rio Grande o Sul are contextualized in the period from 2007 to 2009, mainly through statistical indicators. From this, the study tries to report what was done in terms of political indicators to the referred areas during this allusive period of Yeda Crusius government. The prison and education context in the state and the reflexes of the political proposals to the areas are materialized in a study of case making a contribut ion to the city of Erechim RS, having as object of study the state penitentiary of Erechim, the elementary state school Jaguaretê and the state high school Professor João Germano Imlau. Thereafter, the presumption of an existence of a institutional-political parallel between the prison and the school seek for confirmation. Finally, the text demonstrates such resemblances among the institutions and offers resources for a thinking about the causes and effects of this approach